Do Ocular Fluids Represent a Transmission Route of SARS-CoV-2 Infection? - Petronio Petronio, Giulio; Di Marco, Roberto; Costagliola, Ciro (Frontiers in Medicine, 2021)
The spread of the new SARS-CoV-2 is marked by a short timeline. In this scenario, explaining or excluding the possible transmission routes is mandatory to contain and manage the spread of the disease in the community. In the recent pandemic, it is still unclear how coronavirus can end up in ocular fluids. Nevertheless, eye redness and irritation in COVID-19 patients have been reported, suggesting that conjunctivitis may be an ocular manifestation of SARS-CoV-2 infection. On the basis of epidemiological data provided by previous SARS-CoV infection, numerous theories have been proposed: 1) conjunctiva as the site of direct inoculation by infected droplets; 2) migration of the virus from the upper respiratory tract via the nasolacrimal duct, or 3) haematogenic infection of the tear gland. The demand for further investigations to verify ocular involvement in COVID-19 infection came out from the results of recent meta-analysis studies, so the eye cannot be completely excluded as a transmission route of the infection. Thus, healthcare personnel and all the people that enter in contact with infected or suspected patients must always use the prescribed protective equipment.